Implementasi Metode Forward Chaining pada Sistem Pakar Diagnosis Penyakit Paru - Chandra Setyawan; Mohammad Imron; Abednego Dwi Septiadi (STMIK Sumedang, 2021)
The lungs are one of the important organs to carry out respiratory processes for humans, if the lungs abnormal it will have a negative impact on carrying out other activities. In this case the role of a pulmonary doctor is needed, but its existence in Central Java is still quite a bit and the spread tends to be in big cities. Puskesmas Cilongok 2 is one of the government’s efforts in promoting public health, but until now there has been no lung specialist or adequate medical equipment. Based on this problem, a system is needed which is able to help the community in recognizing the type of pulmonary disease with its handling. One of these application is a website based expert system. The application will be built by applying the forward chaining method. This application allows people to know the type of lung disease based on symptoms entered. In this study, the author uses the waterfall system development method. The results of this study were successfully made an application of expert system diagnosis of lung disease using forward chaining method which was tested on 30 respondents using a likert calculation and showing 86 percent